2021
DOI: 10.1021/acs.jpcb.0c09400
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Light-Harvesting Mechanisms of Type-I Photosynthetic Reaction Centers of Heliobacteria and Photosystem I: Pigment Site Energy Distribution and Exciton State

Abstract: The photosynthetic pigment system on the anoxygenic type-I reaction center of heliobacteria (hRC), which has a symmetrical structure, was analyzed. The excitonic coupling among all of the bacteriochlorophyll g (BChl-g) molecules and chlorophyll a (Chl-a) molecules and the site energy for each pigment were calculated using Poisson-TrESP and the charge density coupling (CDC) methods. The obtained theoretical model reproduced the optical absorption and circular dichroism spectra. It also interpreted the decay-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 53 publications
0
12
2
Order By: Relevance
“…Using the same strategy, we have constructed the exciton models of natural/modified photosynthetic systems of PSI and Heliobacterial RC (hRC) in silico and studied the structure− function relationship. 11,16,17 As a result, our exciton model reproduced the absorption, CD, and decay-associated spectra of hRC and revealed that hRC processes a funnel-like distribution of site energy, in contrast to the non-funnel-like one in TePSI. 17 In this study, we elucidate the light-harvesting mechanism of AmPSI based on its structural information and examine its functional and evolutionary differences.…”
Section: ■ Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Using the same strategy, we have constructed the exciton models of natural/modified photosynthetic systems of PSI and Heliobacterial RC (hRC) in silico and studied the structure− function relationship. 11,16,17 As a result, our exciton model reproduced the absorption, CD, and decay-associated spectra of hRC and revealed that hRC processes a funnel-like distribution of site energy, in contrast to the non-funnel-like one in TePSI. 17 In this study, we elucidate the light-harvesting mechanism of AmPSI based on its structural information and examine its functional and evolutionary differences.…”
Section: ■ Introductionmentioning
confidence: 61%
“…11,16,17 As a result, our exciton model reproduced the absorption, CD, and decay-associated spectra of hRC and revealed that hRC processes a funnel-like distribution of site energy, in contrast to the non-funnel-like one in TePSI. 17 In this study, we elucidate the light-harvesting mechanism of AmPSI based on its structural information and examine its functional and evolutionary differences. The P-TrESP/CDC method was used to obtain the excitonic coupling strength and site energy shift of the exciton Hamiltonian of AmPSI to reproduce the absorption/CD spectra.…”
Section: ■ Introductionmentioning
confidence: 61%
See 3 more Smart Citations